Arte e saúde mental : a criatividade artística como intervenção terapêutica - Monteiro, Ilda (2023)
Therapeutic workshops that use artistic activities allow expressiveness, valuing creativity and ex-pressive fantasy, whose foundation focuses on the concept of creation, strengthening self-esteem and the expression of subjectivities. They are places intended for people with mental health proble-ms, so that they can be inspired and expressed through art, obtaining a new way of existence, relationships and language, with the support and specialized guidance of specialists in the area.The therapeutic work with artistic expressions favors the emotional, biopsychosocial recovery and social integration of these people, through the creative experience, preventing them from serving as a factor of social discrimination. In this sense, it appears that with this experience, the subjects develop their defenses, whether in the emotional or relational field, create life expectations and new skills, and from there achieve a mental ba-lance, as a personal fulfillment whether in the artistic sphere or in other areas. , as it is difficult to achieve “artist status”. This literature review study has as its main objective the inclusion of art in mental health and consequent improvement through artistic practice with the integration of art therapy, drawing as a therapeutic, creative and psychomotor form, art without prejudice inserted in a place to create “O MANICÓMIO”, the creation of an out-of-doors consultation in a public space at the “MAAT” providing the pa-tient with a direct encounter with art, taking into account the analysis of the pathology associated with the creativity and genius of some artists. As an integral part of this development process, an approach was highlighted regarding therapeutic evolutions through art in terms of mental health in order to stop the growing increase of these pathologies.KEYWORDSArt, mind, therapeutic intervention, creativity.